PENGARUH SELF-EFFICACY ( EFIKASI DIRI ) DAN PEMBERDAYAAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI SMAN 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Rahayu, Sari; Salfina, Lili; Meidona, Syofria; Gusmayanti, Fitri (Ensiklopedia of Journal, 2025)
Abstract: This research aims to find out how self-efficacy and human resource empowerment influence employee performance at SMAN 1 V Koto Kampung Dalam Padang Pariaman Regency simultaneously and partially. The research method used is a quantitative method. The sampling technique used is a nonprobability sample with a saturated sampling technique. The data collection techniques used were observation and questionnaires with a sample size of 60 respondents. The analytical method used is multiple linear regression analysis, multiple correlation analysis, and coefficient of determination analysis. It can be seen that the regression equation formed is Y = 10.190 + 0.313X1 + 0.359 X2. The research results show that there is a positive and significant influence between self-efficacy and human resource empowerment on employee performance at SMAN 1 V Koto Kampung Dalam Padang Pariaman Regency. The magnitude of the influence of self-efficacy and human resource empowerment on the performance of employees at SMAN 1 V Koto Kampung Dalam simultaneously is 40.30%. Meanwhile, the influence of self-efficacy on employee performance, the results of partial tests using the t test were 2.728 > t table (1.671) with a probability of 0.008 < 0.05, so there is a significant influence between self-efficacy on employee performance at SMAN 1 V Koto Inner Village. and the effect of human resource empowerment on employee performance is 2,775 > t table (1.671) with a probability of 0.007 < 0.05, so there is a significant influence between human resource empowerment on employee performance at SMAN 1 V Koto Kampung Dalam Padang Pariaman Regency.Keywords: Self-Efficacy, Human Resource Empowerment, Employee Performance.